Model Pop Up Book Keluarga untuk Mempercepat Kemampuan Membaca Anak Kelas Rendah Sekolah Dasar - Siregar, Annisarti; Rahmah, Elva (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2016)
This article aims to understand the technique of family pop-up book for lower grader primary school. Data are collected through interviews, observation, and literature study. Data analysis is done with descriptive qualitative. Based on the data analysis, it is concluded that pop-up book made using techniques and cylinder box – motion technique of moving cube or tube up from the page when a page is opened. As for stages of making pop-up book are, (1) determine the topic, (2) gather together all types of information needed, (3) make design pop-up book, (4) cut pictures, (5) group pictures, (6) make line on the bottom image member family and its size of one cm, (7) prepare background of pop-up, (8) fold paper with balanced size between the two sides and give pressure, (9) specify the paste object pop up and give the point on the side the images as guidelines of paste object, (10) make a line dotted and get sides picture given a last, (11) cut such lines with a cutter, (12) fold the bottom of the image of the object made one cm which is found in the sixth step and put that part of the country into background that has been cut before and give adhesive glue, (13) give garnish on empty part of backlit, (14) name pictures by means of attaching each letter in an appointed backlit, (15) make the cover of pop-up book by using paper and cardboard straw pop-up book family is ready to use. Keywords: pop-up book; reading